2021
DOI: 10.21037/jgo-21-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome variation in colorectal cancer patient with liver metastasis measured by whole-exome sequencing

Abstract: Background: Liver metastasis of colorectal cancer (CRC) is an important cause of death from CRC, but its molecular mechanism is still unclear. In recent years, whole-exome sequencing has played an increasingly important role in the study of the occurrence and development of diseases, especially malignant tumors. Its high throughput and low cost advantages enable researchers to explore the pathogenic genes of diseases, and screen potential molecular markers and therapeutic targets from the level of genomics.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the ubiquitin ligase NEDD4 may be an oncogene in endometrial cancer and may stimulate activation of the IGF-1R/PI3K/Akt signaling pathway (31). Yi et al suggested that the frequently highly mutated genes in CRC liver metastases were mainly enriched in gastric acid secretion, biliary secretion, and melanogenesis (32). Overall, the data of the present study confirmed that RNF215 may be necessary for regulating CRC invasion; nevertheless, more research is required to further elucidate the possible modulatory mechanisms of RNF215 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the ubiquitin ligase NEDD4 may be an oncogene in endometrial cancer and may stimulate activation of the IGF-1R/PI3K/Akt signaling pathway (31). Yi et al suggested that the frequently highly mutated genes in CRC liver metastases were mainly enriched in gastric acid secretion, biliary secretion, and melanogenesis (32). Overall, the data of the present study confirmed that RNF215 may be necessary for regulating CRC invasion; nevertheless, more research is required to further elucidate the possible modulatory mechanisms of RNF215 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 There are multiple etiological factors for CRC, including diet, lifestyle, and genetic susceptibility. 3 , 4 , 5 Hypernutrition, for example, in the form of a Western or high-fat diet (HFD) intake, along with a sedentary lifestyle, is associated with obesity and dyslipidemia, which in turn promote CRC tumorigenesis and progression. 6 Aberrant lipid metabolism is a hallmark of CRC, and obesity and hyperlipidemia are risk factors for CRC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation is an important factor in the occurrence and development of many diseases. Highthroughput sequencing has been widely used in the study of a variety of complex diseases due to its advantages, such as its short consumption time, high throughput, high accuracy, and ability to screen a large number of genes at 1 time, Human whole exome sequencing is a technique to capture and enrich the DNA in the exon region of the whole human genome, and to find genetic mutations related to protein functional variation through high-throughput sequencing (5)(6)(7). Some characteristic mutated genes, such as BRAF (v-raf murine sarcoma viral oncogene homolog B1) and RAF (rat sarcoma viral oncogene homolog), have been identified in melanoma, and highly effective therapies have been developed to target these mutated genes (8,9).…”
Section: Introductionmentioning
confidence: 99%